The Role And Authority Of The National Shariah Council In The Development Of Shariah Economic Law In Indonesia - Alisya Aprilya Dharmayani; Fanny Azelita Humairah; Muhammad Nur Iqbal (SEAN Institute, 2025)
The role and authority of the National Sharia Council (DSN) in push development law sharia economy in Indonesia. DSN is competent authority issue a related fatwa products and services Islamic economics. Therefore that, presence they is tool important For build trust public to system economy based on sharia. The research method used is approach qualitative with analysis legal norms of law, through review to instrument laws, DSN fatwas, and regulations related law Islamic economics in Indonesia. Research results This show that DSN plays a role strategic in align sharia principles and law positive in Indonesia with issued a fatwa that became reference regulation government and actors industry. In addition, DSN plays a role in monitor implementation Sharia principles and educate community and stakeholders interests. However, the challenge covering limitations source power, coordination inter-institutional, and dynamics need industry that continues developing. DSN plays role important in development law Sharia economy in Indonesia. However, for optimize role this, is required more synergy big between DSN, government, and actors industry.